Ten years of conflict management research 2007-2017: An update on themes, concepts and relationships. Issue 1 (11th February 2019) - Caputo, Andrea; Marzi, Giacomo; Maley, Jane; Silic, Mario
Abstract : Purpose: The purpose of this study is to map the intellectual structure of conflict management studies by investigating the key themes, concepts and their relationships for the period 2007-2017. The study updates the previous decade (1997-2006) investigation by Ma et al. (2008 ) to reflect the increased publication efforts in the field. Design/methodology/approach: Bibliometric analysis was used to trace the development path of the extant literature. The study included activity indicators such as distribution of articles and most-cited journals; relationship indicators such as co-author analysis and keyword analysis; and the mapping of the theoretical foundations. Findings: The analysis identified five key themes that help track the direction of conflict management research: negotiation, mediation, trust, conflict management styles and performance. Originality/value: These themes show a wider diversification of topics in the field than in the past, corroborating previous results about the reputation and maturity of conflict management as an independent scientific field of research. This study will help scholars to improve their understanding of the evolution of conflict management studies and the direction that conflict management research is taking, in particular, identifying available avenues for future research.